Voracity, reaction to stings, and survival of domestic hens when feeding on the yellow scorpion (Tityus serrulatus) - Murayama, Gabriel Pimenta; Pagoti, Guilherme Ferreira; Guadanucci, José Paulo Leite [UNESP]; Willemart, Rodrigo Hirata (FapUNIFESP (SciELO), 2022)
Background: Scorpionism is a worldwide problem that has already made thousands of victims, and multi-disciplinary approaches for controlling their populations are to be more successful. Hens are often mentioned as tools for controlling scorpions; however, systematic/experimental behavioral studies are not available. Moreover, there is no systematic information on the effect of scorpion venoms on hens. Using the venomous yellow scorpion Tityus serrulatus, the present study aimed to clarify the following aspects: (1) voracity of hens, (2) how hens react when stung, (3) the effect of scorpion stings on hen behavior during attacks, and (4) hen survivorship after feeding on scorpions. Methods: We attracted hens with corn powder, offered them scorpions and then recorded the hen-scorpion interaction. To test the effects of the sting we manually removed the scorpion’s telson. Results: We found that some hens ate up to six scorpions within minutes. By means of an ethogram and drawings, we showed that they exhibited several aversive behaviors when capturing scorpions. Removal of the scorpion telson stopped the aversive reactions, which was not observed in the control group. Finally, hens did not exhibit atypical behaviors after 1, 7 and 30 days and were all alive after 30 days. Conclusion: This is the first empirical and video recorded study providing evidence that hens are clearly affected by scorpion venom but do not die. Therefore, they may have potential to be used in biological control of these arthropods.
Keywords: Biological control; Buthidae; Natural enemy; Predator-prey interactions